Specific features of the study and maintenance of a potato collection threatened by viruses and virus-like diseases - E. V. Truskinov; M. N. Sitnikov (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. The article deals with the problems faced while studying and maintaining a collection of plant genetic resources against a strong virus infection background.Materials and methods. The data obtained during 8 years of monitoring over 1000 potato accessions for the incidence of virus diseases are presented. The work was carried out at Pushkin and Pavlovsk Laboratories of VIR and at the Polar Experiment Station of VIR (Khibiny, Arctic Circle). Visual control of the symptoms of the infection was combined with an enzyme-linked immunosorbent assay (ELISA) for potato mosaic viruses Х, S, M and Y.Results and conclusions. For many years, the global collection of VIR has been studied and maintained under a threat of strong virus infections. Among the viruses that have the widest distribution and cause significant damage to potato, there are viruses M and Y in Pushkin, and Х in Khibiny. Among the infected plant material, accessions with a latent virus infection, manifesting tolerance to the pathogens, have constantly been observed. The conventional point-based principle of scoring field resistance of potato cultivars and hybrids to viruses requires a significant revision. A new alternative approach is proposed for virus resistance assessment, when the clonal reproduction type of the tested accessions is taken into account.